A study on factors influence the motivation among employees in Flextronics Technology (M) Sdn Bhd / Hasilah Hashim - Hashim, Hasilah (Faculty of Business and Management, 2012)
A study on factors influence the motivation has been conducted among employees in Flextronics Technology (M) Sdn Bhd. The purpose of this study is to identify the dominant factors that influence the motivation among employees invxf this company and the relationship between organizational commitment and job satisfaction towards motivation. 113 questionnaires have been distributed among employees in the company and researcher analyzed the correlation between organizational commitment and job satisfaction towards motivation. Analysis of the data about the motivation among employees in Flextronics Technology (M) Sdn Bhd was very satisfied with their organization and jobs. Thus, the organizational commitment and job satisfaction is the most factors that influence the motivation among direct labours in Flextronics Technology (M) Sdn Bhd.